The multifaceted activities of AMPK in tumor progression—why the "one size fits all" definition does not fit at all?. Issue 11 (November 2013) - Bonini, Marcelo G.; Gantner, Benjamin N.
Abstract AMP‐activated kinase (AMPK) is a central cellular energetic biosensor and regulator of a broad array of cellular metabolic routes activated by nutrient deprivation, mitochondrial dysfunction, oxidative stress, and cytokines. The activation of AMPK maintains ATP levels in response to hypoxia, mitochondrial dysfunction, and shortage of essential metabolic fuels. Activated AMPK turns on energy sparing pathways and promotes antiapoptotic functions thereby permitting cells to survive extremely hostile conditions for prolonged periods of time. Cancer cells in solid tumors are generally subjected to such harsh conditions; however, they manage to efficiently survive and proliferate. This is likely due, in great part, to a peculiar form of metabolism that is heavily reliant on glycolysis and which promotes cancer cell adaptation and tumor progression. AMPK controls the influx and utilization of glucose by cancer cells and therefore has emerged as an attractive target to treat cancer. Investigations exploring this possibility demonstrated that activators or inhibitors of AMPK impact cancer cell viability and possibly cancer progression. For example, the AMPK activator metformin induces apoptosis in a variety of cancer cell lines and models. A major problem with many of the studies on metformin is that little effort has been invested in unraveling how metformin activates AMPK in the many contexts it has been tested. This is significant because many AMPK‐independent effects of metformin have been documented. The notion that AMPK acts solely as a tumor suppressor also conflicts with findings that it confers resistance to nutrient deprivation, sustains NADPH levels in cancer cells, facilitates stress‐induced gene transcription, promotes cell survival via antiapoptotic function upregulation, intermediates epithelial‐to‐mesenchymal transition, and increases malignant transformation. These are all recognized steps necessary for the successful evolution of tumors. This review highlights some of these findings and proposes that the role of AMPK in cancer should be reconsidered in light of the complex roles of AMPK under different metabolic conditions. © 2013 IUBMB Life, 65(11):889–896, 2013